Efektivitas Video Cerita Rakyat Sebagai Media Pembelajaran Untuk Keterampilan Menyimak Pada Peserta Didik Sekolah Dasar - Maghfiroh, Shahifa Putri; Liansari, Vevy (Universitas Hamzanwadi, 2025)
Technological advances have had a significant impact on education, including the use of technology-based learning media. One of the media that can be utilized is folklore videos, which are believed to be able to improve the listening skills of elementary school students. This study aims to analyze the effectiveness of using folklore videos in improving listening skills of grade V elementary school students. The method used in this research is quantitative pre-experimental with a one-group Pre-Test-Post-Test design. The research sample consisted of 24 fifth grade students, who were given a listening test before and after treatment. The data were analyzed using descriptive test to see the increase in the average score, Shapiro-Wilk normality test to test the distribution of data, and Paired Sample T-Test test to see the significance of differences before and after treatment. The results showed that there was a significant improvement in students' listening skills after using folklore videos as learning media. The average Post-Test score is higher than the Pre-Test, and the Paired Sample T-Test results show a significant difference (p < 0.05). This finding indicates that the use of folklore videos is effective in improving students' listening skills. Therefore, it is recommended for educators to utilize video media in learning, in order to increase student engagement and understanding of the material being taught.